2022
DOI: 10.3390/land12010140
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Mapping Spatial Variation Characteristics of Natural Hazards in Pakistan

Abstract: One nation with the highest risk of climate catastrophes is Pakistan. Pakistan’s geographical nature makes it susceptible to natural hazards. Pakistan is facing regional differences in terms of climate change. The frequency and intensity of natural hazards due to climate change vary from place to place. There is an urgent need to recognize the spatial variations in natural hazards inside the country. To address such problems, it might be useful to map out the areas that need resources to increase resilience an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…Atif et al used MODIS data to map the distribution of floods in Pakistan since 2000 and concluded that the central plains and Southeastern Sindh had suffered the most severe floods over the last 21 years [43]. In addition to this, Hussain et al (2023) created a comprehensive database of natural hazards in Pakistan at the district level and a multi-hazard zoning map, indicating that the majority of flood-prone areas are located in Sindh and South Punjab Provinces [44]. Sajjad et al (2020) stated that the Chenab Plain is one of the high flood-prone areas with using remote sensing to estimate the extent and duration of flood inundation in Pakistan [45].…”
Section: Discussionmentioning
confidence: 99%
“…Atif et al used MODIS data to map the distribution of floods in Pakistan since 2000 and concluded that the central plains and Southeastern Sindh had suffered the most severe floods over the last 21 years [43]. In addition to this, Hussain et al (2023) created a comprehensive database of natural hazards in Pakistan at the district level and a multi-hazard zoning map, indicating that the majority of flood-prone areas are located in Sindh and South Punjab Provinces [44]. Sajjad et al (2020) stated that the Chenab Plain is one of the high flood-prone areas with using remote sensing to estimate the extent and duration of flood inundation in Pakistan [45].…”
Section: Discussionmentioning
confidence: 99%
“…Landslide susceptibility varies from area to area based on factors such as surface geology, moisture availability, proximity to seismically active zones, and slope angle (Hussain et al, 2023). Quantitative techniques dominated in landslide vulnerability modeling.…”
Section: Landslide Disaster Vulnerabilitymentioning
confidence: 99%